Effect of mineral salts, vitamins and gelling agents on somatic embryogenesis in Coffea arabica L. ‘Catuai Influência dos sais minerais, vitaminas e agentes gelificantes, na embriogénese somática de Coffea arabica L. ‘Catuai’ - Maria Cristina Simões-Costa (Revista de Ciências Agrárias, 2010)
Somatic embryogenesis was induced in leaf explants of Coffea arabica ‘Catuai’. A two steps procedure was followed: explants were first cultured in a callus induction medium containing 2,4-dichlorophenoxyacetic acid and 6-benzylaminopurine and later transferred to an auxin free embryo induction and conversion medium. The influence of three mineral salt formulations: Schenk & Hildebrandt (1972) full salt solution, Murashige & Skoog (1962) full and half salt solutions; two vitamin mixtures: Gamborg et al. (1968) and Schenk & Hildebrandt (1972) and two gelling agents: agar and gelrite, was assessed. Best embryogenic response was obtained in culture medium with Schenk & Hildebrandt (1972) mineral salts, Gamborg et al. (1968) vitamins and agar. In this medium, somatic embryos were observed after 18 weeks of culture and, six weeks later, 85% of the explants presented an average of 18 somatic embryos per explant. Foi induzida embriogénese somática em explantados foliares de Coffea arabica ‘Catuai’. A metodologia seguida incluiu duas fases: os explantados foram cultivados inicialmente em meio de indução de callus, suplementado com ácido 2,4-diclorofenoxiacético e 6-benzilaminopurina, tendo sido depois transferidos para meio sem auxina, com o objectivo de induzir a formação e o desenvolvimento de embriões. Testou-se a influência de três diferentes composições de sais minerais: sais minerais de Schenk & Hildebrandt (1972), sais minerais (concentração completa e ½ concentração) de Murashige & Skoog (1962); duas formulações vitamínicas: Gamborg et al. (1968) e Schenk & Hildebrandt (1972) e dois agentes gelificantes: agar e gelrite. A melhor resposta relativamente à embriogénese somática foi registada em meio de cultura com os sais minerais de Schenk & Hildebrandt (1972), as vitaminas de Gamborg et al. (1968) e agar. Neste meio de cultura verificou-se a presença de embriões somáticos após 18 semanas de cultura e, seis semanas mais tarde, 85% dos explantados apresentavam, em média, 18 embriões somáticos por explantado.